Common learning and cooperation in repeated games. Issue 3 (6th July 2020) - Sugaya, Takuo; Yamamoto, Yuichi
Abstract : We study repeated games in which players learn the unknown state of the world by observing a sequence of noisy private signals. We find that for generic signal distributions, the folk theorem obtains using ex post equilibria. In our equilibria, players commonly learn the state, that is, the state becomes asymptotic common knowledge.